STROKE PREVENTION IN HYPERTENSIVE PATIENTS - S. Y. Martsevich; V. A. Egorov (Рациональная фармакотерапия в кардиологии)
Importance of the stroke as one of the main reason of population mortality and invalidity is considered. Stroke risk factors including arterial hypertension are described. The main pharmacotherapy ways of primary and secondary stroke prevention are discussed.